RJFA 2021
DOI: 10.7176/rjfa/12-23-03
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Statement Fraud Using the Fraud Hexagon Model

Abstract: This study aims to obtain empirical evidence about the fraud hexagon theory. The research was conducted on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sampling method used was non-probability sampling with purposive sampling technique. There are 42 companies as a population with a total of 35 companies as a sample. The data analysis technique used is multiple linear regression. Based on the results of the analysis, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The results showed that the number of CEO photos affected financial statement fraud, as evidenced by the sig value of 0.025 (<0.05), which explains that the number of CEO photos attached to financial reports is a form of power politics and individual ego. The results of this study are in line with research [36], which reports that the arrogance described here is the attitude of someone who feels that internal controls and company policies do not apply to him. He believes that these things are not binding on him, so he has the potential to commit more significant acts of fraud.…”
Section: Frequent Number Of Ceo's Picturesupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the number of CEO photos affected financial statement fraud, as evidenced by the sig value of 0.025 (<0.05), which explains that the number of CEO photos attached to financial reports is a form of power politics and individual ego. The results of this study are in line with research [36], which reports that the arrogance described here is the attitude of someone who feels that internal controls and company policies do not apply to him. He believes that these things are not binding on him, so he has the potential to commit more significant acts of fraud.…”
Section: Frequent Number Of Ceo's Picturesupporting
confidence: 90%
“…Financial stability plays an essential role as a proxy in assessing a company's performance which will later become a reference for decision-making and an attraction for external parties to the company. Therefore, the higher total assets in a company will increase the interest of investors and other stakeholders so that the company's internal parties are encouraged to present financial reports according to their needs [36]. The study results show that the financial stability variable affects fraudulent financial statements because it has a sig 0.023 below 0.05.…”
Section: Financial Stabilitymentioning
confidence: 91%
“…The results of this study are consistent with the research conducted by Pranyanita et al, (2021) and Sudrajat et al, (2023) which state that collusion has no effect on the tendency of fraudulent financial reporting. However, it is not consistent with the research conducted by Aviantara, (2021), Erliani et al, (2023) and Ketaren et al, (2023) which state that collusion does affect the propensity to engage in fraudulent financial reporting.…”
Section: The Effect Of Collusion On the Tendency Of Fraudulent Financ...supporting
confidence: 92%